Spatial and temporal distribution of macrobenthos communities and their relationship with secondary front in Hangzhou Bay - Jia, Kangning; Tang, Yanbin; Liu, Qinghe; Zhang, Rongliang; Liao, Yibo; Shou, Lu; Zeng, Jiangning; Chen, Quanzhen; Chen, Jianfang (Frontiers in Marine Science, 2022)
Water quality in Hangzhou Bay is inferior (grade 5) because of discharge from Yangtze River and Qiantang River, and from factories around the bay. We analyze relationships between the environment and macrobenthic communities at 44 stations throughout Hangzhou Bay, based on samples collected in 2006, from 2016–2018, and in 2021. Long-term spatial and temporal changes in macrobenthos, and the influence of secondary water fronts on community composition, are discussed. Macrobenthos in Qiantang River Estuary is numerically, primarily dominated by crustaceans, and elsewhere by polychaetes. Species that differ most in abundance between four identified regions in the bay are the amphipod Corophium sinensis, clam Potamocorbula laevis, and polychaete Amaeana occidentalis. The abundance and biomass of macrobenthos in different regions differs significantly. Taxa are allocated to six feeding guilds: filter feeders and omnivores predominate in Qiantang River Estuary and south of Hangzhou Bay, while surface and subsurface deposit feeders predominate in sediments north of Hangzhou Bay and in the bay mouth area. Negative correlations are apparent between the abundances of polychaetes Nephtys polybranchia, Magelona japonica, Heterospio sinica, Sabella sp. and A. occidentalis and salinity and pH, while positive correlations are apparent between those of Sternaspis scutata and Capitellidae sp. The numbers and biomasses of macrobenthic species in the Hangzhou Bay frontal area increase significantly relative to values in adjacent areas. The difference of each area near the front is more than 94%, and the main difference species are polychaetes and mollusks. Our baseline data for this region might ultimately contribute towards improved conservation of regional macrobenthos, and a better understanding of ecosystem health in this highly polluted bay.